TRANSFORMASI DAN IMPLEMENTASI PRODUK PEMBIAYAAN NON BAGI HASIL DALAM PERBANKAN SYARIAH DI INDONESIA: STUDI SYSTEMATIC LITERATURE REVIEW ATAS AKAD HAWALAH, RAHN, DAN QARD: TRANSFORMASI DAN IMPLEMENTASI PRODUK PEMBIAYAAN NON BAGI HASIL DALAM PERBANKAN SYARIAH DI INDONESIA: STUDI SYSTEMATIC LITERATURE REVIEW ATAS AKAD HAWALAH, RAHN, DAN QARD - Azifah Hidayati; Syukri Iska; Fandi Ahmad Marlion (JURNAL KAJIAN ISLAM MODERN, 2026)
This article presents the results of a Systematic Literature Review (SLR) to analyze the transformation, implementation, challenges, and opportunities of non-profit-loss sharing financing products in Islamic banking in Indonesia, with a specific focus on ḥawālah, rahn, and qard contracts. This study aims to explore the evolving dynamics of non-profit-loss sharing financing instruments, examine their compliance with Sharia principles, and identify structural as well as operational challenges in their implementation within Islamic financial institutions. This research employs a qualitative SLR approach by reviewing scholarly publications from 2019 - 2024, sourced from reputable databases such as Scopus, ScienceDirect, and Google Scholar. Using the PRISMA protocol, a total of N = 20 relevant articles were systematically selected and analyzed, revealing a significant growth of approximately 65% in publications since 2021, indicating increasing academic attention to non-profit-loss sharing financing. The key findings indicate a significant shift from social-oriented (tabarru’) functions toward commercial (tijarah) orientations, particularly in the implementation of rahn. Meanwhile, ḥawālah remains underutilized despite its potential role in liquidity management and debt restructuring. On the other hand, qard continues to play a crucial role in promoting financial inclusion, although it faces sustainability constraints in terms of funding sources. However, the study also identifies major challenges, including a trade-off between Sharia compliance, operational efficiency, and financial sustainability, as well as weak integration of risk management and Sharia-based governance frameworks. The effectiveness of these financing products heavily depends on strengthening Sharia governance, enhancing product innovation, and improving Islamic financial literacy among the public. The main contribution of this study lies in emphasizing that the development of non-profit-loss sharing financing products requires an integrative approach grounded in maqāṣid al-sharī‘ah, ensuring that financial practices are not only profit-oriented but also aligned with broader socio-economic welfare and justice objectives.